2009
DOI: 10.1111/j.1467-8535.2008.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

The further development of CSIEC project driven by application and evaluation in English education

Abstract: In this paper, we present the comprehensive version of CSIEC (Computer Simulation in Educational Communication), an interactive web-based humancomputer dialogue system with natural language for English instruction, and its tentative application and evaluation in English education. First, we briefly introduce the motivation for this project, survey the related works and illustrate the system structure with flow diagram. Then we describe its pedagogical functions, especially free chatting and chatting on a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…From another perspective, Ryu and Han (2017) examined the images of artificial intelligence in students' minds and found that students described AI as innovative and unprecedented. In some studies, the use of artificial intelligence in the education of children has been evaluated as an interesting and motivating experience for researchers and teachers (Akdeniz, 2019;Kamite et al, 2019;Jia & Chen, 2009;Keleş & Aytürk Keleş, 2002;Kolchenko, 2018). Furthermore, it can be seen that children are positively affected by the process, particularly when chatbots are used in education.…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, Ryu and Han (2017) examined the images of artificial intelligence in students' minds and found that students described AI as innovative and unprecedented. In some studies, the use of artificial intelligence in the education of children has been evaluated as an interesting and motivating experience for researchers and teachers (Akdeniz, 2019;Kamite et al, 2019;Jia & Chen, 2009;Keleş & Aytürk Keleş, 2002;Kolchenko, 2018). Furthermore, it can be seen that children are positively affected by the process, particularly when chatbots are used in education.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes toward the program vary between learners though. University students tend to engage more and perceive a higher utility for such systems than high school or middle school students (Ehsani, Bernstein & Najmi, 2000;Jia & Chen, 2009). Two studies also showed that intrinsically motivated learners engaged and benefited more from the software (Anderson et al, 2008;Baur et al, 2015).…”
Section: Survey Studiesmentioning
confidence: 99%
“…Quest Atlantis, Second Life, and SIMS) to perform simulations have also been reported to reduce anxiety among ELLs and promote language learning (Cole & Griffiths, 2007;Jia & Chen, 2009;Rinalli, 2008;Sha, 2009;Thorne, Black, & Sykes, 2009;Zheng et al, 2009). According to Cole and Griffiths, using MUVEs for simulations reduces the anxiety levels of the student and allows for more authenticity and engagement in communication.…”
Section: Chapter Summarymentioning
confidence: 99%